ANALISA PENGARUH PARAMETER SISTEM PENGKONVERSIAN WET GAS TERHADAP PERFORMA KOMPRESOR SENTRIFUGAL - Ambo Intang (TEKNIKA: Jurnal Teknik, 2014)
Within a specific operation, depending on the operation and maintenance, the compressor will experience performance degradation or performance as a result of increased and decreased several operating parameters compression of gas. To determine the effect of changing the operating parameters of the loss in performance then do retrieval and data processing operations on the wet gas compressor (WGC) FCCU unit Revenary III Pertamina Plaju by comparing with the operating specifications satandar (design) it. From the calculation results can be seen that the current Wet Gas Compressor Efficiency polytropis has declined, to Section I of 80.1% design to be 79.4% (down 0.7%) and section II of 77.6% design to 71, 2% (down 6.4%). As a result of a decrease Efficiency, then Shaft Horse Power has increased from 1981.48 kW design to 2156.487 kW (up by 8.5%). The fall in efficiency compressor polytropis main cause is the occurrence of fouling on the side of Compressor Blade-blade which is marked by higher operating temperature (TOP) and the increased pressure drop on the other hand decreased compressibility Wet gas is not so significant effect on changes in gas deinsitas. Keyword : Centrifugal Compressor, Parameters, Permorma, Pengkompresian Wet Gas